An Evaluation of a cognitive-behavioral intervention for depressive and anxiety symptoms in children and adolescents: a quantitative study (Brazilian Journal of Behavioral and Cognitive Therapy, 2026)
Child Regulation Therapy (TRI) regulates the cognitive model of anxiety and depression in children and adolescents. TRI has cultural sensitivity, develops skills and has the participation of parents. This study seeks to verify the effectiveness of TRI for anxious and depressive symptoms and in reducing inappropriate patterns in the cognitive triad. The objective is to evaluate the effect of TRI on children and adolescents aged 8 to 12 years, measuring symptoms of anxiety, depression and the cognitive triad. Quantitative and retrospective study with pre and post-tests on 18 participants. Analysis carried out by an independent evaluator. Instruments used: Screen for Child Anxiety Related Emotional Disorders, Childhood Depression Inventory and Cognitive Triad Inventory for Children. Results: positive effect on the negative self, with reduction in negative beliefs about oneself. There was no effect on anxious/depressive symptoms. The regulation of the cognitive triad is related to healthy development in adulthood.
Keywords: cognitive behavior therapy; child; Depression